UNRAVELING THE COMPLEXITY OF PUBLIC TRANSPORT GOVERNANCE IN URBANIZED AREA: CASE STUDY OF YOGYAKARTA URBANIZED AREA - Devi, Mutiasari Kurnia; Miharja, Miming; Furqan, Alhilal (Built Environment Studies, 2024)
Transport governance has become an increasingly significant aspect of transport research. In urban areas, the institutional problems become more complex since they involve actors across administrative regions, not to mention institutional fragmentation, where actors need to have the capabilities to build good coordination between institutions. In addition, Indonesia currently has weak institutional capacity in public transportation planning and policy. This can hinder the development of effective and efficient public transportation. This paper elaborates on the complexities of public transportation planning in the Yogyakarta Urbanized Area (YUA) by unraveling the distribution of responsibilities and coordination mechanisms across governance levels. To fulfill this objective, we conduct interviews with policy-makers and stakeholders involved in public transport policy-making. Unclear roles, limited financial and human resources, and the lack of a clear institution responsible for public transport arrangements within YUA are constraints to achieving successful public transport planning in YUA. However, YUA has a typical polycentric governance system involving multiple actors in the public transport policy-making process, aggravating the coordination problem in various horizontal and vertical networks between actors.